2011
DOI: 10.1111/j.1365-2699.2010.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting alpha diversity of African rain forests: models based on climate and satellite-derived data do not perform better than a purely spatial model

Abstract: Aim Our aim was to evaluate the extent to which we can predict and map tree alpha diversity across broad spatial scales either by using climate and remote sensing data or by exploiting spatial autocorrelation patterns.Location Tropical rain forest, West Africa and Atlantic Central Africa.Methods Alpha diversity estimates were compiled for trees with diameter at breast height ‡ 10 cm in 573 inventory plots. Linear regression (ordinary least squares, OLS) and random forest (RF) statistical techniques were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Our results are similar to those of Parmentier et al (2011), who found that kriging predictions of rainforest tree diversity were as good as regression-based ones-among other techniques-, but also that the performance of all techniques was good in well-sampled areas and bad in poorly inventoried territories. Kriging and other related techniques such as co-kriging can be used for interpolating spatially autocorrelated data (Legendre & Legendre 1998), but their success in extrapolating the dependent variable to new geographical domains will depend on how consistent is its spatial structure across the studied region; in our case, on how stationary are the spatial trends in species richness.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results are similar to those of Parmentier et al (2011), who found that kriging predictions of rainforest tree diversity were as good as regression-based ones-among other techniques-, but also that the performance of all techniques was good in well-sampled areas and bad in poorly inventoried territories. Kriging and other related techniques such as co-kriging can be used for interpolating spatially autocorrelated data (Legendre & Legendre 1998), but their success in extrapolating the dependent variable to new geographical domains will depend on how consistent is its spatial structure across the studied region; in our case, on how stationary are the spatial trends in species richness.…”
Section: Discussionsupporting
confidence: 79%
“…Kriging is much less used for this purpose (but see e.g. Ter Steege et al 2003;Parmentier et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As strategies for conserving species and communities focuses as much on species richness and endemism (Myers et al 2000, Lovett et al 2000, Kier and Barthlott 2001, more detailed information about the coastal forests of Cameroon, especially on the poorly known Ngovayang Massif, is necessary. Better data from such unexplored areas would greatly increase the reliability of modeling patterns of tree alpha diversity in African rain forests (Parmentier et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to Franklin (1998) and Shataee et al (2012), nearest neighbours, support vector machine and random forest, which can do both classification and regression, are the most common algorithms among data mining algorithms. Many researchers used these algorithms to model the quantity of forest characteristics (Ismail, Mutango 2010;O'Sullivan et al 2010;Parmentier 2011;Yazdani 2011;Shataee et al 2012). Moreover, the advantages of non-parametric algorithms rely on the fact that they are not sensitive to a high number of independent variables as inputs for modelling.…”
mentioning
confidence: 99%
“…Some of the ecological factors which can affect biodiversity are elevation, aspect, slope, climate, and human activities (Ejtehadi et al 2010). So far there are different kinds of studies that have been conducted in different territories, trying to predict or investigate diversity distribution related to topographic factors (Pourbabaee 1998;Marvie Mohajer 2005;Gracia et al 2007;Ismailzadeh, Hosseini 2007;Ghanbari 2008;Saatchi et al 2008;Kymasi 2012), edaphic (Qomioghli et al 2006;Ejtehadi et al 2010;Kymasi 2012) and climatic factors (Mehdinya et al 2006;Parmentier 2011;Gixhari et al 2012). One of the main purposes of modelling research is to clarify the most appropriate method, regarding the spatial prediction of forest characteristics, based on sampling methods (Kint et al 2003).…”
mentioning
confidence: 99%